Tinjauan Hukum Islam Tentang Pengalihan Barang Gadai Tanpa Sepengetahuan Pemiliknya - Syaik Abdillah; Imam Mudin Hasbuloh (Jurnal Hukum Ekonomi Syariah, 2026)
Pawn transactions are a form of contract in muamalah intended to provide debt security. However, in practice, deviations often occur, one of which is the transfer of pawned goods without the owner’s consent. This phenomenon is quite common in Karangtengah Village, Kadungora Sub-district, Garut Regency, where pawned goods such as motorcycles are transferred by the pawnee (murtahin) to third parties without the approval of the pledger (rahin). The main research problems are how Islamic law regulates pawn rights and the protection of the owner, how the transfer is practiced in the local community, and how Islamic law views such practices. The purpose of this study is to provide a comprehensive understanding of the legal status of pawn transfers according to sharia, while assessing their implications for justice and trust in transactions. This research employs a qualitative descriptive method, using interviews with local residents and related documentation. The findings reveal that unauthorized transfers violate sharia principles, including the rule of ghasab (unlawful appropriation), and reflect the community’s weak legal awareness. In conclusion, this practice is invalid under Islamic law. Therefore, legal education, greater community awareness, and the implementation of written contracts are needed to uphold justice and trust in pawn transactions. Keywords: Pawn; Transfer; Islamic Law; Trust; Ghasab.